2021
DOI: 10.3389/fmicb.2021.637427
|View full text |Cite
|
Sign up to set email alerts
|

Marine Peptide-N6NH2 and Its Derivative-GUON6NH2 Have Potent Antimicrobial Activity Against Intracellular Edwardsiella tarda in vitro and in vivo

Abstract: Edwardsiella tarda is a facultative intracellular pathogen in humans and animals. There is no effective way except vaccine candidates to eradicate intracellular E. tarda. In this study, four derivatives of marine peptide-N6NH2 were designed by an introduction of unnatural residues or substitution of natural ones, and their intracellular activities against E. tarda were evaluated in macrophages and in mice, respectively. The minimum inhibitory concentration (MIC) value of N6NH2 and GUON6NH2 against E. tarda was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…After treatment with peptides, the bacteria were washed twice with PBS and stained with propidium iodide (PI). Finally, a flow cytometer (FACS Calibur, BD, USA) was applied to determine the fluorescence [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…After treatment with peptides, the bacteria were washed twice with PBS and stained with propidium iodide (PI). Finally, a flow cytometer (FACS Calibur, BD, USA) was applied to determine the fluorescence [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…168 Moreover, synergistic antibacterial effects can be achieved by conjugating AMPs with other compounds, including CPPs or antibiotics. [169][170][171][172] Wang and coworkers constructed two CPP-AMP conjugates (B6N2 and T11N2) and found that these conjugates mainly locate in endosomes of RAW264.7 macrophage cells. Moreover, these conjugates exhibited enhanced activity against intracellular S. typhimurium as compared to AMP alone or non-conjugated mixtures.…”
Section: Antimicrobial Peptides and Their Conjugatesmentioning
confidence: 99%
“…In addition, esculentin-1a-derived peptides can penetrate the plasma membrane of bronchial cells and promote the rapid clearance of intracellular Pseudomonas aeruginosa since there is a ~ 40% and 60% decrease in the number of intracellular bacteria one hour after exposure ( 83 ).. Likewise, peptides like N6NH2 and their derivative, GUON6NH2, can be internalized in infected macrophages and exert their antibacterial activity against Edwardsiella tarda , thus helping reduce intracellular bacterial numbers ( 84 ). Another peptide that was able to enter murine and human macrophages in vivo is mature bovine neutrophil β-defensin 4.…”
Section: Amps Against Intracellular Bacteriamentioning
confidence: 99%